Comparative Performance of Selected Soil Inoculant, Soil Amendment, and Foliar Fertilizer in Enhancing Upland Rice Production (American Journal of Agricultural Science, Engineering, and Technology, 2025)
The rising cost of farm inputs (fertilizers) results in higher production expenses in rice farming; thus, meeting the country’s growing demand for food is at stake due to a lack of capital for production. The agriculture department pinned several strategies to boost rice production through new varieties and mechanization to secure food sufficiency. Contributing to boosting rice production was why this study was encapsulated, and evaluating the efficacy of selected soil inoculants, soil conditioners, and organic foliar fertilizers on agronomic yield and yield components of rice (NSIC Rc 27) was the objective. A completely randomized block design was used in the study (RCBD) with eight (8) treatments: T1 = Farmers Practice (FP), T2 = Recommended Rate of Fertilizers (RRF) Application, T3 = Soil Inoculant Application (SIA), T4 =Foliar Fertilizer Application (Carrageenan) (FFA), T5 = Soil Amendments Application (SAA) combined with soil Inoculants (CRH and Bacillus amyloliquefaciens), T6 = Foliar Fertilizer combined with soil inoculant, T7 = 50% RRF combines with Foliar Fertilizer and soil inoculant and T8 = 50% RRF combines with soil inoculant and replicated thrice in a 4m x 5m standard size with a total area of 646m2 with the duration of two years. The research was conducted at Davao de Oro State College’s research laboratory at Compostela, Davao de Oro. Agronomic parameters, meteorological data, yield and yield components, and economic analysis were collected. The results confirmed that various approaches increased upland rice production by up to 3.9 tons per hectare. On the other hand, soil conditioners and soil inoculants like carbonized rice hull (CRH) and Bacillus spp could improve soil health by increasing organic matter, resulting in better absorption of nutrients correlating to higher production.